2019
DOI: 10.1002/alr.22451
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a preclinical model for training and assessment of cerebrospinal fluid leak repair in endoscopic skull base surgery

Abstract: BackgroundAchieving an effective endoscopic skull base reconstruction in case of large dural defects requires specific training and can be extremely challenging. The aim of this study was to describe the development and validation of a preclinical model for cerebrospinal fluid (CSF) leak repair, which can be used for training and to test the mechanical efficacy of endoscopic skull base reconstruction.MethodsEleven fresh‐frozen cadaver heads were dissected. A catheter was inserted in the subdural space via a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Although ENT surgeons are directly involved in the surgical procedure, neurosurgeons are necessarily involved to manage and choose complex dural and intracranial reconstruction and to treat eventual complications. Therefore, surgeons need intensive training to acquire surgical skills and experience 50,51 . To date, no adequate risk stratification to outline reconstructive algorithms still exist.…”
Section: Discussionmentioning
confidence: 99%
“…Although ENT surgeons are directly involved in the surgical procedure, neurosurgeons are necessarily involved to manage and choose complex dural and intracranial reconstruction and to treat eventual complications. Therefore, surgeons need intensive training to acquire surgical skills and experience 50,51 . To date, no adequate risk stratification to outline reconstructive algorithms still exist.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Mattavelli et al reported a similar preclinical model, in which they measured CSFL pressure points. 11 Some limitations exist concerning this model. First, the studied group was not compared to a control group that can use other CSFL models.…”
Section: Discussionmentioning
confidence: 99%
“…reported a similar preclinical model, in which they measured CSFL pressure points. 11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations